Effect of Acetazolamide on Pulmonary Hemodynamics and Right Heart Function in Healthy Adults Going to Altitude: A Randomized Controlled Trial - Mayer, Laura; Lichtblau, Mona; Furian, Michael; Buergin, Aline; Saxer, Stéphanie; Mademilov, Maamed; Bader, Patrick R.; Schneider, Simon R.; Sooronbaev, Talant; Bloch, Konrad E.; Ulrich, Silvia (Journal of the American Heart Association, 2025)
Exposure to high altitude triggers hypoxic pulmonary vasoconstriction with a rise in pulmonary artery pressure (PAP). This may lead to symptomatic pulmonary hypertension with impaired right heart function and exercise capacity. We investigated whether preventive acetazolamide treatment would attenuate the altitude-induced PAP-increase and hereby improve hemodynamics in nonacclimatized middle-aged healthy lowland residents ascending to 3100 m. In this placebo-controlled, double-blind parallel trial, healthy lowland residents >40 years living <800 m, were randomized to acetazolamide (375 mg/day) or placebo during a 48-hour stay at 3100 m, starting 24 hours before ascent. Echocardiography was performed at 760 m before medication and repeated after the first night at 3100 m. Systolic PAP, hemodynamics, and surrogates of right heart function were compared between the 2 groups. The analysis included 171 healthy, 33% female subjects, age 53±7 years (mean±SD), randomized to placebo (n=82) or acetazolamide (n=89). The primary outcome, systolic PAP at 760/3100 m, was 22.0±0.8/26.6±0.7 mm Hg under placebo versus 21.6±0.7/24.1±0.6 mm Hg under acetazolamide with a mean altitude effect difference (acetazolamide-placebo, treatment effect) of -2.5 (95% CI, -5.3 to 0.4) mm Hg ( =0.087). Significant treatment effects with acetazolamide were detected for saturation by pulse oxymetry 2 (1 to 2)%, heart rate -5 (95% CI, -9 to -1)/minute, cardiac output -0.8 (95% CI, -1.3 to -0.4) L/min, oxygen delivery -123 (95% CI, -211 to -34) mL/min, and fractional area change of -4 (95% CI, -7 to -0)%. In healthy, middle-aged lowland residents traveling to 3100 m, preventive acetazolamide tended to but did not significantly attenuate the altitude-induced PAP-increase. An alteration of hemodynamics and right heart function was observed resulting in a reduced overall oxygen delivery, which may counter the proven positive effects of acetazolamide on arterial oxygenation and acclimatization process. URL: https://clinicaltrials.gov; Unique Identifier: NCT03540914.